Nonlinear control of grid-connected wind energy conversion system without mechanical variables measurements - Karim Noussi; Abdelmajid Abouloifa; Hanane Katir; Ibtissam Lachkar; Fouad Giri (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This article addresses the problem of controlling an overall wind energy conversion system (WECS) formed by a wind turbine connected to the grid via a doubly fed introduction generator (DFIG) and an AC/DC/AC converter. The main control objectives are fourfold: (i) designing an output feedback speed controller that makes the DFIG rotate at the optimal value delivered by the MPPT strategy, (ii) controlling the stator reactive power so as to be null, (iii) guaranteeing the DC-link voltage in the grid side converter to be at a given constant value, (iv) ensuring a unitary power factor. A high gain observer is synthesized, in order to provide estimated values of the mechanical variables. To achieve the control objectives, a sliding mode controller involving the mechanical observer is designed. The performance of the system configuration based on the 2MW-DFIG with the proposed controller is evaluated by a numerical simulation under a realistic wind profile using MATLAB/SIMULINK/SimPowerSystems environment.